Acute Effects of Olive Leaf Tea and Olive Leaf Powder Biscuits on Postprandial Glycemia, Lipid Profile and Inflammatory Markers: A Randomized Controlled Crossover Trial in Healthy Volunteers - Panagiota Potsaki; Olga I. Papagianni; Kalliopi Almpounioti; Charalampos Soulakellis; Angeliki Voutsa; Olga Katira; Vasiliki Bountziouka; Charalampos Karantonis; Antonios E. Koutelidakis (Applied Sciences, 2025)
Postprandial dysmetabolism, which refers to the impaired regulation of glucose and lipid levels after meals, is recognized as an independent risk factor for cardiovascular diseases (CVDs). Diets rich in polyphenols have demonstrated potential in improving postprandial hyperglycemia and hyperlipidemia. This study investigates the effects of olive leaf polyphenols on postprandial metabolic outcomes following a high-fat and high-carbohydrate meal. A total of 36 healthy adults participated in a three-arm randomized crossover trial. They ingested either a biscuit made from olive leaf powder (OLB), olive leaf tea (OLT), or a placebo meal (CTRL) to assess the impact of olive leaf polyphenols on postprandial glycemia, lipid levels, platelet aggregation factor (PAF), and plasma antioxidant status (TAC). Although no statistically significant differences were observed in the primary biomarkers, including glucose and lipid profiles, a delayed insulin response was noted in the interventions involving olive leaf. These findings suggest that while acute olive leaf supplementation did not significantly alter postprandial glycemia or lipidemia, it may subtly influence insulin kinetics. Further research is needed to explore the long-term effects of olive leaf polyphenols on metabolic health, especially in populations at risk for CVDs.